THE ROLE OF ENTREPRENEURSHIP EDUCATION IN MITIGATING UNEMPLOYMENT RATES AMONG UNIVERSITY GRADUATES IN SOUTH AFRICA - Bongani T. Gamede; Oluwatoyin Ayodele Ajani (International Journal of Innovative Technologies in Social Science, 2024)
This scoping review investigates the role of entrepreneurship education in mitigating unemployment rates among university graduates in South Africa. The study seeks to understand how entrepreneurship education can equip graduates with the necessary skills to create job opportunities for themselves and others, thus addressing the high unemployment rates prevalent in the country. A comprehensive literature search was conducted, accessing 230 publications, out of which 57 peer-reviewed articles were selected for detailed analysis. The review synthesizes existing research on the effectiveness of entrepreneurship education programs, highlighting successful case studies and identifying common barriers to their implementation. Findings suggest that entrepreneurship education can significantly enhance graduates' employability by fostering entrepreneurial mindsets, skills, and behaviours. The review also identifies key components of effective entrepreneurship education programs, such as practical training, mentorship, and the integration of real-world business challenges into the curriculum. However, the study also highlights challenges, including inadequate funding, lack of trained educators, and insufficient industry collaboration. To address these issues, the study recommends policy reforms, increased investment in entrepreneurship education, and stronger partnerships between universities and the private sector. By implementing these strategies, South African higher education institutions can better prepare graduates for entrepreneurial ventures, thereby reducing unemployment rates and stimulating economic growth.